FITRAH MANUSIA DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM DI ERA 4.0 - Asep Wijaya (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2023)
Abstract Humans are born with various potentials that exist in them and that is a basic human nature that must be developed optimally to make a complete human being, one of which is through the process of Islamic education. This study aims to determine the relationship between human nature and the world of Islamic education. The method used is a qualitative research method with a Library Research design. The data collection technique is by looking for relevant sources, both books, and journals with national reputations. As for the analysis using content analysis (content analysis). The results of the study show that in humans there is a nature that must be developed, namely: 1) Religious nature, 2) Reasonable nature, 3) Hygiene nature, 4) Moral/Akhalak nature, 5) Independence nature, 6) Truth nature, 7) Justice, 8) Equality, 9) Individual nature, 10) social nature, 11) sexual nature, 12) economic nature, 13) political nature, 14) artistic nature. All the potentials of human nature in the era of 4.0 are so unstoppable that they bring many children who cannot develop their potential properly, even in a negative direction which is very concerning. Therefore, Islamic education is related to the development of the potential of human nature because in it there are systems that regulate child development and of course, the values ​​taught are Islamic values ​​based on the Qur'an and Sunnah. So that it will direct children in perfecting the potential that exists in them.